Pengaruh Rasio Likuiditas dan Rasio Solvabilitas Terhadap Kinerja Keuangan Perusahaan Sub Sektor Ritel yang Terdaftar di Bursa Efek Indonesia Periode 2021-2024 - Anastasya A; Eulin Karlina (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
In recent years, global and national economic shifts have significantly impacted the financial stability of companies, including those in Indonesia's retail sub-sector. This study aims to analyze the effect of liquidity and solvency ratios on the financial performance of retail sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period. The variables used include Current Ratio (CR) as a measure of liquidity, Debt to Asset Ratio (DAR) as a measure of solvency, and Return on Assets (ROA) as an indicator of financial performance. A quantitative approach was employed. The results show that, partially, CR does not have a significant effect on ROA. Meanwhile, DAR has a positive and significant effect on ROA. Simultaneously, CR and DAR have a significant effect on ROA. These findings indicate that although liquidity alone does not significantly impact profitability, the combination of liquidity and solvency plays a crucial role in determining the financial performance of retail companies. This study is expected to serve as a valuable reference for management and investors in assessing corporate financial health.